Writer Žemaitė’s (Artistic) Life Reconstruction According to Archival Documents - Ruseckaitė, Aldona (Bibliotheca Lituana, 2018)
[full article and abstract in Lithuanian; summary in English] The surviving private writings and egodocuments of Julija Žymantienė-Žemaitė (1845–1921), a classic of Lithuanian literature, are rather numerous. The writer wrote her autobiography, which does not cover her whole life; it describes the period up to the beginning of her creative path, around 1892, but this autobiographical work provides plenty of facts from her life: the noble descent of her parents, the writer’s childhood, youth, first studies, marriage, troubles of marital life, her thirst for reading and education. Where the autobiography ends, Žemaitė’s autobiographic stories can help us recreate her life, i.e. Pasiklausymai (Overhearings), Iš mano atsiminimų (From My Memories), Iš baudžiavos laikų (From the Times of Serfdom), Pirmieji mano žingsniai (My First Steps), Kalėjime (In Prison), etc. Her piece of writing Povilas Višinskis created in America in 1916 where Žemaitė recalls her first creative steps is especially important. A separate group of egodocuments – Žemaitė’s letters to Povilas Višinskis (1875–1906), a journalist, literary critic and the writer’s neighbour – can be distinguished. Over 70 letters survived to our days. The letters reveal the very beginning of her creative work, its twists and turns and the writer’s doubts when she sent nearly every short story or play she wrote to her young friend expecting his criticism or approval. Her later letters exhibit self-confidence, versatile personality development. Žemaitė’s letters to her dear friend and beloved person Konstantinas Petrauskas (1878–1947) make up yet another group of egodocuments. Whereas the letters to Višinskis focus on creative work, love prevails in this case. Žemaitė wrote over 60 letters to Petrauskas during the period 1911–1921. Their correspondence displays Žemaitė’s late love and its vitality rendering special shades and traits to her personality as well as provides a broad panorama of the political and cultural life of Vilnius in 1911–1915.